2009
DOI: 10.1074/jbc.m109.009605
|View full text |Cite
|
Sign up to set email alerts
|

Human Mitochondrial SUV3 and Polynucleotide Phosphorylase Form a 330-kDa Heteropentamer to Cooperatively Degrade Double-stranded RNA with a 3′-to-5′ Directionality

Abstract: Efficient turnover of unnecessary and misfolded RNAs is critical for maintaining the integrity and function of the mitochondria. The mitochondrial RNA degradosome of budding yeast (mtEXO) has been recently studied and characterized; yet no RNA degradation machinery has been identified in the mammalian mitochondria. In this communication, we demonstrated that purified human SUV3 (suppressor of Var1 3) dimer and polynucleotide phosphorylase (PNPase) trimer form a 330-kDa heteropentamer that is capable of efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
109
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 51 publications
6
109
0
Order By: Relevance
“…Apart from our study, a number of additional potential substrates for hPNPase old-35 have been identified, including small RNA and noncoding RNA. Very recently, Wang et al (17) described a model whereby mitochondrial hPNPase old-35 forms a heteropentameric complex with a helicase hSUV3 that functions in a coordinated manner to degrade dsRNA substrates in the presence of ATP. Mechanistically, helicase (hSUV3) unwinds the RNA substrate, and the exoribonuclease present in the same entity can efficiently degrade the structured RNA (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from our study, a number of additional potential substrates for hPNPase old-35 have been identified, including small RNA and noncoding RNA. Very recently, Wang et al (17) described a model whereby mitochondrial hPNPase old-35 forms a heteropentameric complex with a helicase hSUV3 that functions in a coordinated manner to degrade dsRNA substrates in the presence of ATP. Mechanistically, helicase (hSUV3) unwinds the RNA substrate, and the exoribonuclease present in the same entity can efficiently degrade the structured RNA (18).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from c-myc mRNA degradation, hPNPase old-35 is also involved in regulating the levels of several small noncoding RNAs (16). Very recently, Wang et al (17) reported that hPNPase old-35 , along with human mitochondrial SUV 3 (suppressor of Var1 3), degrades dsRNA in the 3′-to-5′ direction. Considering the above findings, it seemed plausible that hPNPase old-35 would have an impact on the other small RNAs, like miRNAs.…”
mentioning
confidence: 99%
“…ATPase Assay, Gel Mobility Shift Assay, Helicase Assay, and Exoribonuclease Assay-Experimental procedures were adapted from a previous publication (40,41), and detailed procedures can be found in the supplemental Experimental Procedures. All DNA and RNA oligonucleotides were purchased from Integrated DNA Technologies (San Diego, CA) Sequences included T20DNA (5Ј-CAA ACT CTC TCT CTC TCA AC), 3WLRNA (5Ј-GUU GAG AGA GAG AGA GUU UGA GAG AGA GAG GUU UGA GAG AGA), and T22RNA (5Ј-CUC AAA CUC UCU CUC UCU CAA C).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent purification procedures using nickel beads were based on a previous publication (40). His-tagged DSS1 was co-transformed into Rosetta with pREP4 plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…It is an essential component of the mitochondrial degradosome complex that regulates mtRNA decay and mRNA surveillance (19). Human SUPV3L1 is important for maintaining mitochondrial homeostasis (20) and has been shown to degrade double-stranded RNA (21). However, SUPV3L1 also appears to function in the cytoplasm, interacting with the WRN and BLM DNA helicases to suppress mitotic homologous recombination (13).…”
Section: Discussionmentioning
confidence: 99%